Cloning, expression and sequence analysis of anthocyanidin synthase gene BcANS in Brassica campestris var. purpurea - JIANG Ming; CHEN Xiao-shang; LI Jin-zhi (浙江大学学报. 农业与生命科学版)
PCR primers were designed according to BaANS gene isolated from Brassica albograbra, and the gene, designated BcANS, was amplified from cotyledons DNA and cDNA of B. campestris var. purpurea, respectively. The gene sequence was submitted to NCBI with an accession number of GQ120562. Genomic DNA was 1 637 bp in length with one 560 bp intron, and the complete coding sequence was 1 077 bp encoding 358 amino acids. RT-PCR results showed that BcANS expressed in cotyledons and hypocotyls under light condition, and there was no expression under dark condition. BcANS expressed under dark and light conditions in phosphorus-deficient medium. However, higher expression levels in cotyledons and hypocotyls were observed under light condition. Sequence alignment results revealed higher homology between BcANS and those of B. oleracea, B. juncea and Arabidopsis thaliana. Low similarity was observed between BcANS and those of Gramineae plants, indicating their distant evolutionary relationships. Isolation, sequence analysis of anthocyanidin synthase gene in B. campestris var. purpurea laid the foundation for further study of gene function and anthocyanin biosynthesis mechanisms.